(3cJGH GjSbdGhS aj GdeWGdYs - (3GjSbdGhSs
(3ChdgG (B:s
(3GPG cGfJ ebGOjQ YOJgG RhL cebGOjQ hgj eJJGdjI hRjGOI HYVgG Ydi HYV eJSGhjI s
(3BNQgG (B:s
(3hGPG YQafG eWGdY GdLRA hcGfJ GdRjGOGJ eYdheI aeWGdY LejY GdCLRGA eYdheI hPdc eG GQOfGg Je cJGH GSJjbdGhS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi YTQs
(3GfXQg eY GdeNWhW Qbe (B66 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1459s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(11/2432) s
Keywords: (3Gdadcs